Dissection of synechococcus rubisco large subunit sections involved in heterologous holoenzyme formation in escherichia coli - Ong, Wei Chi (2023)
Ribulose-1,5-bisphosphate carboxylase/oxygenase (Rubisco) catalyzes fixation of atmospheric CO2 into organic carbon ribulose-1,5-bisphosphate (RuBP) in the Calvin cycle of photosynthesis. Yet, its slow catalysis and inability to differentiate CO2 from O2 for fixation into RuBP make it a target for genetic engineering to improve its catalytic properties as a prospect for improving photosynthetic efficiency to raise crop yield. Unfortunately, formation of functional Rubiscos in heterologous host has been a challenge due to chaperone incompatibility. In Escherichia coli, prokaryotic Rubiscos form holoenzyme whereas eukaryotic Rubiscos form insoluble aggregates. As studies have shown, GroEL-GroES chaperonin mediates folding of Rubisco large subunit (RbcL) in E. coli, it is hypothesized that GroEL does not recognize eukaryotic RbcL as substrate protein. A previous study reported a few regions of cyanobacterial RbcL from Synechococcus PCC6301 to be important for successful holoenzyme formation in E. coli. This study aims to further narrow-down the potential GroEL recognition (GR) regions by breaking down these regions into six smaller regions (each with 25 amino acid residues), replacing them with their counterpart sequence of green iii algal Chlamydomonas reinhardtii RbcL, and checking their influences on holoenzyme formation in E. coli. If swapped regions of Synechococcus RbcL are important for are important for GR, no formation of chimeric Rubisco should be observed. Therefore, six chimeric Rubiscos were constructed. Besides, examined RbcL regions were screened for potential GR sites based on the hydropathicity (GRAVY) value of GroES mobile loop sequence. Moreover, as non-assembly could also be due to global protein instability imparted by the structural destabilization effect of mutations, any loss of interaction arises from mutations were also predicted. Assembly analysis, based on native polyacrylamide gel electrophoresis (PAGE) showed residues 248-272, 273-297, 348-372 and 423-447 could be essential for GR whereas residues 373-397 and 398-422 are not. Moreover, site-directed Rubisco mutants with single mutations were created to examine their individual impacts on Rubisco assembly. Substitution of residues 348-372 of Synechococcus RbcL by the Chlamydomonas counterpart introduced eight mutations and resulted in non-assembly. Interestingly, these eight mutations did not result in non-assembly individually but some of them reduced the amount of assembled enzyme.